Irrigation adoption: A potential avenue for reducing food insecurity among rice farmers in Benin - Nonvide, Gbêtondji Melaine Armel (My University, 2018)
Since the 1960s, the government of Benin has invested in the development of canal irrigation schemes in order to intensify food crop production and reduce food insecurity. This paper employed an ordered probit model with sample selection to assess the potential of irrigation in reducing food insecurity in the municipality of Malanville, Benin. The results show that 60% of the irrigation farmers and 46% of the dry land farmers were food secure. Adoption of irrigation has a positive effect on food security. Other variables explaining food security are education, informal training, credit, extension services, use of improved seed, fertilizer and herbicide application, farm and off-farm income. The study recommends that efforts to rehabilitate current irrigation scheme and develop other schemes should be intensified.
Keywords: Irrigation; Food insecurity; Item response theory; Rasch model; Ordered probit model